PENGEMBANGAN STRATEGI PEMBELAJARAN AKTIF DAN KREATIF DALAM PENDIDIKAN KRISTEN - Imanuel Catur Oktanto Suryoadi (TANGKOLEH PUTAI, 2022)
In the world of education, strategy is defined as a plan that contains a series of activities designed to achieve educational goals, namely, students actively and creatively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, and society. nation and state. The reality is that students are only smart theoretically, but poor in application. Any subject cannot develop an attitude that is in accordance with religious norms, because the learning process is only directed so that students can master and memorize the subject matter so that not a few of the students have decreased interest in learning, experience boredom in carrying out learning, do not participate actively and creative in learning, failed to answer questions correctly and some students did not make changes after getting follow-up actions.